(untitled) (Acta Scientiarum. Health Sciences, 2019)
Health is defined by the World Health Organization as a state of complete physical, mental and social well-being, and not merely the absence of disease. The present study aimed to know and reflect on the perception of the indigenous ethnicity Haliti-Paresí on the health-disease process. It is a research with a qualitative and ethnographic approach, in which data were collected in July 2015, through visits in the Wazare village and dialogue with the 34 residents, followed by the constitution of core meanings for data separation, according to their nature. The Paresí define health as the state of vitality in which there is energy to perform the basic activities, with food, hygiene and spirituality as determining factors. Negligence by the individual, climate change and higher forces establish the disease, with hantavirus being the main and most worrying. The health-disease process is based on the culture of this people, in which there is the figure of the shaman, elder or chief to reestablish the vital balance through rituals, offerings, teas and prayers, associated with Western medicine. There should be greater training of indigenous and non-indigenous professionals to provide comprehensive and effective assistance, as well as health education as a tool for disease prevention.